Messinian age and savannah environment of the possible hominin Graecopithecus from Europe - Böhme, M.; Spassov, N.; Ebner, M.; Geraads, D.; Hristova, L.; Kirscher, Uwe; Kötter, S.; Linnemann, U.; Prieto, J.; Roussiakis, S.; Theodorou, G.; Uhlig, G.; et al. (Public Library of Science, 2017)
Dating fossil hominids and reconstructing their environments is critically important for understanding human evolution. Here we date the potentially oldest hominin, Graecopithecus freybergi from Europe and constrain the environmental conditions under which it thrived. For the Graecopithecus-bearing Pikermi Formation of Attica/Greece, a saline aeolian dust deposit of North African (Sahara) provenance, we obtain an age of 7.37-7.11 Ma, which is coeval with a dramatic cooling in the Mediterranean region at the Tortonian-Messinian transition. Palaeobotanic proxies demonstrate C4-grass dominated wooded grassland-To-woodland habitats of a savannah biome for the Pikermi Formation. Faunal turnover at the Tortonian-Messinian transition led to the spread of new mammalian taxa along with Graecopithecus into Europe. The type mandible of G. freybergi from Pyrgos (7.175 Ma) and the single tooth (7.24 Ma) from Azmaka (Bulgaria) represent the first hominids of Messinian age from continental Europe. Our results suggest that major splits in the hominid family occurred outside Africa.